The influence of computer anxiety on experienced computer users while performing complex computer tasks. - Beckers, John J.; Rikers, Remy M. J. P.; Schmidt, Henk G. (Computers in Human Behavior, 2006)
This study was conducted to test the hypothesis whether computer anxiety has a hindering effect on experienced computer users while performing complex computer tasks. Participants were 75 third-year psychology students taking a Delphi programming course. Prior to the course, a computer anxiety scale was filled in. Computer performance was measured in four different ways: through final course grade, predicted final grade, self-perceived programming skills, and through observed behavior while programming a computer application. The results showed that computer anxiety was found to correlate with the students' prediction of their final grade and with the perception of their own computer skills, but had no effect on actual performance as measured by the final course grade. Furthermore, there was no significant effect of computer anxiety on behavioral measures while students were programming a computer application. The findings point into the direction of a “threshold effect”, where anxiety only hinders performance when this anxiety is sufficiently severe or when the context in which the task to be executed on a computer is ambiguous. Copyright (c) 2006 Elsevier Ltd